Meneliti hubungan jihad perniagaan dengan pencapaian usahawan muslim berjaya di Malaysia = [Examining the relationship between business jihad and the achievement of successful muslim entrepreneurs in Malaysia] - Yaacob, Y.; Azmi, I.A.G. (Penerbit Universiti Kebangsaan Malaysia, 2015)
This research aims to examine the relationship between business jihad and the achievement of Muslim entrepreneurs in Malaysia. In addition, this study also aims to determine the validity of the construct of jihad business by understanding the extent of the research instrument in defining jihad business operationally and to confirm the most suitable dimensions. There are four main dimensions in this study, jihad against lust, knowledge jihad, property jihad and human jihad which encompasses 23 items. The findings from factor analysis revealed that only two dimensions remained in the business jihad factor which are property jihad and human jihad, therefore excluding 16 items from the 23 items discussed. The Cronbach's alpha value for property jihad is 0.73 and for human jihad is 0.71. The correlation and regression analysis show that there is a positive relationship between property jihad and human jihad towards the achievement of Muslim entrepreneurs in Malaysia.